2015
DOI: 10.1073/pnas.1502301112
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling activates a positive feedback mechanism involving insulin-like growth factors to induce osteoblast differentiation

Abstract: Hedgehog (Hh) signaling is essential for osteoblast differentiation in the endochondral skeleton during embryogenesis. However, the molecular mechanism underlying the osteoblastogenic role of Hh is not completely understood. Here, we report that Hh markedly induces the expression of insulin-like growth factor 2 (Igf2) that activates the mTORC2-Akt signaling cascade during osteoblast differentiation. Igf2-Akt signaling, in turn, stabilizes full-length Gli2 through Serine 230, thus enhancing the output of transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 54 publications
1
67
0
Order By: Relevance
“…The present study has shown that activation of GDNF/RET/AKT signaling inhibits the GSK3β activity and subsequently induces the proteolytic formation of GLI activators including GLI2-A and GLI3-F, resulting in increases in GLI activators and activation of HH signaling, thereby promotes the proliferation of NB cells and tumor growth. Our findings not only correspond to previous findings demonstrating that the synergy between PI3K/AKT and HH signaling occurs in embryonic development and HHdependent tumors, and that Igf2-AKT stabilizes full-length Gli2 through Serine 230 and in turn enhances the output of transcriptional activation by HH, but also correspond to previous observations indicating that AKT inhibits GSK3β activity in a variety of signaling pathways, such as Wnt, insulin, SHH, and mTOR pathways [35][36][37][38][39]. Since AKT is able to activate mammalian target of rapamycin (mTOR)/S6 kinase 1 (S6K1) and in turn promotes GSK3β-independent increases in GLI transcriptional activity and GDNF promotes mitogenic effect in SH-SY5Y cells through AKT and S6K1 signaling [40,41], in the present study, we are still unable to exclude the possibility that GDNF/RET/AKT activates HH signaling through mTOR/S6K1 pathway.…”
Section: Discussionsupporting
confidence: 92%
“…The present study has shown that activation of GDNF/RET/AKT signaling inhibits the GSK3β activity and subsequently induces the proteolytic formation of GLI activators including GLI2-A and GLI3-F, resulting in increases in GLI activators and activation of HH signaling, thereby promotes the proliferation of NB cells and tumor growth. Our findings not only correspond to previous findings demonstrating that the synergy between PI3K/AKT and HH signaling occurs in embryonic development and HHdependent tumors, and that Igf2-AKT stabilizes full-length Gli2 through Serine 230 and in turn enhances the output of transcriptional activation by HH, but also correspond to previous observations indicating that AKT inhibits GSK3β activity in a variety of signaling pathways, such as Wnt, insulin, SHH, and mTOR pathways [35][36][37][38][39]. Since AKT is able to activate mammalian target of rapamycin (mTOR)/S6 kinase 1 (S6K1) and in turn promotes GSK3β-independent increases in GLI transcriptional activity and GDNF promotes mitogenic effect in SH-SY5Y cells through AKT and S6K1 signaling [40,41], in the present study, we are still unable to exclude the possibility that GDNF/RET/AKT activates HH signaling through mTOR/S6K1 pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Ablation of Smo in fibroblasts instigated the noncanonical activation of GLI2 expression, and GLI2 directly regulated Tgfa expression. The mechanism involved AKT-dependent phosphorylation of Ser230 in GLI2, which, previous work demonstrated, leads to enhanced stability and transactivation activity (Shi et al 2015). The stroma undergoes a dramatic expansion in concert with the stepwise development of human PDAC, suggesting that the stroma is an active partner in PDAC initiation and progression (Feig et al 2012).…”
Section: Discussionmentioning
confidence: 97%
“…AKT-GLI2 signaling is activated in Smo-deleted fibroblasts GLI2 is stabilized through phosphorylation of residue Ser230 by AKT, resulting in increased expression of downstream target genes (Shi et al 2015). To test whether the observed increase in GLI2 protein in KCS cells could be due to AKT-dependent phosphorylation, GLI2 was immunoprecipitated from KS and KCS fibroblasts, and its phosphorylation status was determined by Western blot analysis using an antibody specific for phospho-(Ser/Thr) AKT substrates (Zhang et al 2002).…”
Section: Tgf-α Is Up-regulated In Smo-deleted Fibroblasts and Promotementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Hedgehog (Hh) signaling, a critical inducer of the early steps of osteoblast differentiation, has been reported to stimulate aerobic glycolysis in both muscle and brown adipose tissue through a non-canonical mechanism [38,39]. Although a similar metabolic regulation by Hh has not been described during osteoblast differentiation, Hh signaling has been shown to induce Igf2 expression via Gli2, resulting in mTORC2 activation in the osteogenic progenitors [40]. Thus, it will be of interest to examine the potential relationship between Hh signaling and glycolysis in bone formation.…”
Section: Glucose Metabolism In Osteoblastsmentioning
confidence: 99%